2010
DOI: 10.1161/strokeaha.110.585240
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cognitive Outcomes With Endovascular Coiling of Ruptured Intracranial Aneurysms

Abstract: Background and Purpose-The International Subarachnoid Aneurysm Trial (ISAT) reported lower rates of death and disability with endovascular versus neurosurgical treatment of ruptured intracranial aneurysms. However, assessment of functional outcome was limited to the modified Rankin Scale, which is known to be insensitive to cognitive function. A neuropsychological substudy (N-ISAT) was therefore done in all recruits from 8 ISAT centers in the United Kingdom. Methods-Detailed neuropsychological assessment was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(28 citation statements)
references
References 33 publications
(36 reference statements)
0
27
1
Order By: Relevance
“…Coil embolization may reduce these symptoms without brain retraction and perforation injury. 24,25 Although the aneurysm size has also been reported to be an important risk factor associated with outcome, 16 the results of the present study indicated no association between aneurysm size and poor outcome. Generally, in direct surgical treatment of large and giant aneurysms, more brain manipulation such as retraction and dissection may be needed to obtain a sufficient operative field, resulting in poor outcome.…”
Section: Discussioncontrasting
confidence: 53%
“…Coil embolization may reduce these symptoms without brain retraction and perforation injury. 24,25 Although the aneurysm size has also been reported to be an important risk factor associated with outcome, 16 the results of the present study indicated no association between aneurysm size and poor outcome. Generally, in direct surgical treatment of large and giant aneurysms, more brain manipulation such as retraction and dissection may be needed to obtain a sufficient operative field, resulting in poor outcome.…”
Section: Discussioncontrasting
confidence: 53%
“…Previous studies showed that patients with clipped aneurysms have a higher incidence of neurocognitive deficits and seizures compared with patients with coiled aneurysms. 1,2 However, it remains unknown if patients with clipped aneurysms also have a higher incidence of other in-hospital complications such as pneumonia or myocardial infarction.…”
mentioning
confidence: 99%
“…First, the dichotomous GOSE may be insensitive to clinically important effects of pharmaceutical treatments on outcomes. 1,41 Second, the variability of the doses in the studies may have affected the results. Therefore, the explanation for the dissociation between vasospasm-related morbidity and clinical outcomes may have been unclear, but it is of importance for the design of new clinical trials.…”
Section: 30mentioning
confidence: 99%